PENGARUH DIMENSI KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN GELAMAI MERK ERINA KECAMATAN PAYAKUMBUH BARAT KOTA PAYAKUMBUH - Kartika, Cici Lia; Natassia, Rizky; Sari, Mareta Kemala (Pendidikan Ekonomi, 2013)
ABSTRACTThis study aims to reveal : 1) How does the performance of the consumers to buy the brand gelamai Erina District West Payakumbuh; 2) How does the feature of the consumers to buy the brand gelamai Erina Payakumbuh West District; 3) How does the reliability of the consumers to buy the brand gelamai Erina Payakumbuh western districts; 4) How does the conformation of the consumers to buy the brand gelamai Erin a District West Payakumbuh; 5) How does durability to consumers to buy brands Erina gelamai District West Payakumbuh; 6) How does the esthetic of the consumers to buy the brand gelamai Erina District western Payakumbuh; 7) How does the quality of the product dimension to the consumers to buy the brand gelamai Erina District west Payakumbuh Object of study is the consumer brand gelamai Erina District West Payakumbuh.Â The study population was all consumer brands gelamai Erina District West Payakumbuh Payakumbuh consumers with a sample of 100 people. The data analysis technique used is multiple regression.Based the results of statistical tests, using the t test showed that the variable performance, feature, reliability, conformance, durability and esthetics has a significant level <0.05 so that these variables have a significant influence on consumer buying interest gelamai brands Erina. Based on the calculation of F count, together variables of product quality have significant level <0.05, it is proved that these variables significantly influence buying interest gelamai brands Erina. Based on the test results of the calculation of the coefficient of determination (R Square) showed that consumers to buy brands Erina gelamai influenced by variable performance, feature, reliability, conformance, durability and esthetic of 33.8%, while the remaining percentage of 66.2% is explained by other variables or causes beyond regression models of this study.Â Keywords : Dimensions of Product Quality, buying interest, multiple linear regression